Functional Assessment of Elderly Patients after Stroke - Biercewicz, Monika (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2020)
Introduction. A history of neurological disease often exerts a strong influence on the patient’s further life in four basic dimensions: functional, mental, social and spiritual.Aim. The aim of the study was to perform a functional assessment of an elderly patient after a stroke and to verify whether selected demographic and clinical factors have a significant impact on functional capacity.Material and Methods. The research was carried out in the Department and Clinic of Geriatrics, University Hospital no. 1 of A. Jurasz in Bydgoszcz on a group of 88 patients after stroke. Functional status was assessed using the Barthel Index — BI, depressive disorders were assessed using the Geriatric Depression Scale — GDS, and higher cognitive functions were assessed using the Mini-Mental State Examination — MMSE.Results. As a result of the statistical analysis, no statistically significant differences were found in the functional capacity of the patient in the individual measurements (first and second) of Friedman’s ANOVA (N = 88, df 1) = 0.32; p = 0.582, which means that the patients were classified into the same functional capacity groups, obtaining a similar result in repeated measurements. It was found that gender, age and the number of comorbidities had a statistically significant (p < 0.05) effect on the functional status of the subjects. There was no statistically significant influence of the place of residence (p > 0.05) and family situation (p > 0.05) on the functional status of the respondents. A statistically significant correlation was also found between depressive disorders (Spearman’s rank -0.438; p < 0.05) and disorders of higher cognitive functions (Spearman’s rank -0.548; p < 0.05) and functional capacity.Conclusions. In the majority of cases, elderly patients regain functional independence after a stroke. Men showed better functional fitness. Older age and more comorbidities worsen functional performance. It has also been found that the functional state is interdependent with cognitive and emotional disorders. (JNNN 2020;9(2):59–64)